Distribution of phytoplankton in Kuantan Port, Malaysia during northeast monsoon season = Taburan fitoplankton di Pelabuhan Kuantan, Malaysia semasa musim monsun timur laut - Hamzah, Amir Safwan; Mohammad Noor, Normawaty; Adam, Aimimuliani; Ahmad, Zuhairi (The Malaysian Analytical Sciences Society, 2019)
Harmful algal bloom (HAB) is a proliferation of phytoplankton that can produce bio toxins and cause harm to human health, as well as the environment and the organisms associated with it. The first case of HAB in Kuantan Port was recorded in November 2013, followed by another outbreak in August 2014. This study aims to investigate the phytoplankton distribution and dispersal in the Kuantan Port during the Northeast monsoon season in order to identify the extent of the spread of HAB, should such an event occur again. Phytoplankton samples were taken at Kuantan Port from three levels of depth (surface, middle, and bottom) at every hour during a period of 24 hours. Samples were preserved in Lugol’s iodine. Chemical properties such as phosphorus, nitrate, nitrite, and ammonia were also taken during each sampling. Phytoplankton samples were counted and identified up to genus level. Simulation of phytoplankton dispersal in Kuantan Port was conducted using the program MIKE 21. RMSE error was conducted to improve accuracy between ADCP data and simulated data, and was found to be within acceptable range. The MIKE 21 simulation showed that the algal bloom would remain inside the port and would not spread out to the sea. Thirty-seven taxa of phytoplankton were identified. Phytoplankton concentrations ranged from 124 cells/L to 775 cells/L. TSS value ranged from 0.0110 mg/L to 0.0345 mg/L. Phosphorus concentration ranged from 0.075 mg/L PO4 to 3.82 mg/L PO4. Nitrate concentration ranged from 1.05 mg/L NO3-N to 2.45 mg/L NO3-N. Nitrite concentration ranged from 0.0040 mg/L NO2-N to 0.0095 mg/L NO2-N. Ammonia concentration ranged from 0.045 mg/L NH3-N to 0.140 mg/L NH3-N. A positive correlation was found between phytoplankton abundance and nutrient concentration of phosphorus, nitrate and ammonia, with a slightly negative correlation for nitrite. This study recorded the presence of several HAB species such as Dinophysissp, Noctillucasp, and Prorocentrum sp. The presence of these species further indicates that several safety measures need to be considered to safeguard public health, particularly in the coastal waters of Pahang.